2017
DOI: 10.1016/j.tem.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinase Regulation in Hepatic Metabolism

Abstract: The mitogen-activated protein kinases (MAPKs) participate in a multitude of processes that control hepatic metabolism. The liver regulates glucose and lipid metabolism and under pathophysiological conditions, such as obesity, type 2 diabetes mellitus, and non-alcoholic fatty liver disease these processes become dysfunctional. Stress responses activate the hepatic MAPKs which, is thought to impair insulin action and lipid metabolism. The MAPKs also activate the MAPK phosphatases which, oppose their actions. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
116
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 59 publications
3
116
2
Order By: Relevance
“…Mechanistically, Dusp9 protects against NASH mainly through restraining ASK1–JNK/p38 signaling. In the liver, JNK/p38 signaling plays a central role in processes that control hepatic metabolism . In brief, JNK1 directly perturbs hepatic lipid metabolism by regulating PPARα and facilitates IR by promoting serine phosphorylation of IRS1 in hepatocytes .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanistically, Dusp9 protects against NASH mainly through restraining ASK1–JNK/p38 signaling. In the liver, JNK/p38 signaling plays a central role in processes that control hepatic metabolism . In brief, JNK1 directly perturbs hepatic lipid metabolism by regulating PPARα and facilitates IR by promoting serine phosphorylation of IRS1 in hepatocytes .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to these regulators, Dusp9 belongs to the MAPK phosphatase (MKP) family. MAPK hyperactivation in turn activates the MKPs to oppose their action, which forms a feedback regulation loop . Thus, targeting Dusp9–ASK1 signaling, a physiological regulation loop, may provide an effective and reliable strategy for NASH treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in addition to increased lipogenic and gluconeogenic genes, HMGCR KI mice exhibited enhanced macrophage infiltration and elevated proinflammatory cytokine Il6 expression. In NAFLD subjects, both nuclear factor kappa B and mitogen‐activated protein kinase pathways were found to be enhanced and have a direct correlation with hepatic inflammation and fibrosis . Thus, it is possible that these pathways may also indirectly mediate some of the phenotypes besides the up‐regulation of cholesterol synthesis in HMGCR KI mice…”
Section: Discussionmentioning
confidence: 99%
“…In NAFLD subjects, both nuclear factor kappa B and mitogen-activated protein kinase pathways were found to be enhanced and have a direct correlation with hepatic inflammation and fibrosis. (45,46) Thus, it is possible that these pathways may also indirectly mediate some of the phenotypes besides the up-regulation of cholesterol synthesis in HMGCR KI mice Recently, Woods et al (47) reported that mice expressing a constitutively active form of AMPK (γ1-Asp316Ala) in the liver were protected from developing hepatic steatosis on a high-fructose diet. These mice had essentially the reciprocal phenotype to the HMGCR KI mice that develop steatosis on a high-carbohydrate diet.…”
Section: Discussionmentioning
confidence: 99%